Digital Approaches to Arabic Language Learning: Content Strategies and Audience Engagement on Educational Instagram Accounts - Hikmah, Khizanatul; Amrullah, Muhlasin; Abiyyah, Azhar Arij; Yani, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2025)
The development of social media can accelerate, simplify, and improve the performance of educators to be more efficient and effective, thereby increasing productivity. Educators have begun to innovate in the learning process by utilizing the Instagram platform. Through this platform, many educational accounts have been found that provide information and knowledge, including Arabic language learning. This article presents the engagement and content strategies of three Instagram accounts (@kursuskuba, @kampungarab_pare, and @marhaban academy) in designing Arabic language learning. The research design used by the researcher employs content analysis with a descriptive qualitative approach. The analysis process was carried out through the stages of data reduction, data display, verification, and conclusions. Three Instagram accounts, KUBA, Marhaban Academy, and Kampung Arab Pare, utilize the Reels, Feed, Stories, Polling, Live, Quiz, and Q&A features to increase audience engagement and make Instagram an adaptive learning medium. KUBA emphasizes vocabulary, grammar, and interactive exercises; Marhaban focuses on vocabulary with engaging visuals; while Kampung Arab Pare emphasizes everyday communicative expressions. The findings of this study contribute to a deeper understanding of how digital content strategies and audience engagement can be optimized to support Arabic language learning, providing practical insights for educators, content creators, and language institutions in designing more effective and engaging learning experiences through social media platforms.